Performance Analysis and Dimensional Optimization of 2RUPaR-2RRU Parallel Mechanism - Linxian Che; Bing He; Jie Li; Haiyi Jiang (Jixie chuandong)
A novel plane symmetric 2RUPaR-2RRU parallel mechanism with two translational and two rotational degrees of freedom is proposed， and it is can be used as the main body structure of a vibrating screen. The screw theory is applied to analyze its degrees of freedom and to identify the motion characteristics. The displacement analysis model is established to obtain the analytical expressions of inverse displacement solutions to this mechanism. This study analyzes the velocity of the mechanism by means of the vector method and derives the input and output Jacobian matrices. On this basis， the possible singular configurations of the mechanism are investigated. The input and output transmission indices are used to evaluate the motion and force transmission performances of the mechanism. Furthermore， the definition， the numerical calculation method of the effective transmission orientation workspace and the effective transmission positional workspace （ETPW） are introduced. A constrained optimization model is constructed to formulate the design problem of dimensional parameters on the maximizing ETPW， and the differential evolutionary algorithm is employed to solve this problem. A case of dimensional optimization design of the mechanism is given to show that the presented model and algorithm are feasible and effective. The ETPW of the mechanism obtained by optimization design is better than that obtained by the experience design.